CREATION BASIC FUNCTIONS FOR THREE-DIMENSIONAL SIMPLEX ELEMENTS - Сеничак, Василь Михайлович; Сеничак, Владислав Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The objective of the research is creation basic functions for three-dimensional simplex type linear elements used in numerical methods for solving engineering problems – finite element method (FEM).